Penggunaan Media Kartu untuk Meningkatkan Hasil Belajar Materi Penjumlahan dan Pengurangan Bilangan Bulat - Muhammad Ilham Rosyadi; Ziroatun Nusha (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
This study aims to improve the learning outcomes of material addition and subtraction of integer grade 2 MI Ma'arif NU Sekaran by using positive negative number card media. Positive negative number card media can help students in building real concepts of integers. This research is a Classroom Action Research (CAR), which is one type of research used to improve the quality of learning both the results and the learning process. The subjects in this study were the students of grade 2 MI Ma'arif NU Sekaran with a total of 22 students, consisting of 10 male students and 12 female students. The object in this study is the result of learning mathematics. Data collection methods used in this study were observation and tests with research instruments namely observation sheets and evaluation questions. The data analysis technique used in this research is descriptive qualitative and quantitative descriptive data analysis. The results showed that using positive negative number card media could improve learning outcomes of addition and reduction of integer material. In the quality of learning, after the implementation of the first cycle, the teacher's activities in teaching and student participation are in the good category. In the second cycle increased to very good. Improved learning outcomes shown by increasing the average value of learning outcomes before being given an action that is 63.63 with completeness achieved by 6 students (27.27%), increased in the first cycle with an average learning achievement test of 78.86 with completeness achieved 12 students (54.54%) were in the good category. In cycle II the class averagerose to 82.5 with completeness achieved by 17 students (77.27%) and in the very good category.